On averaging of stochastic systems of integrodifferential equations with the «Poisson noise» - Kolomiets , V. G.; Melnikov , A. I.; Muhitdinov , T. M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
An analog of N. N. Bogolyubov’s theorem is proved concerning averaging, on a finite time interval, of a system of integral-differential equations with a ≪Poisson noise≫.